COVID-19 and Sexual Desire: Perceived Fear Is Associated with Enhanced Relationship Functioning. Issue 4 (4th May 2022) - Rodrigues, David L.; Lehmiller, Justin J.
ABSTRACT: Lifestyle changes caused by the COVID-19 pandemic had mostly negative consequences for individual, relationship, and sexual functioning. However, some individuals have reported increases in sexual desire and made new additions to their sex lives. Given that stress-provoking situations can sometimes make mortality more salient and heighten sexual desire, it is possible that lifestyle changes and fear of COVID-19 infection may have benefited some relationships. We conducted a cross-sectional study with 303 romantically involved adults (58.1% men) and found that lifestyle changes were associated with negative changes in one's sex life, unrelated to wanting to spend time with one's partner, and positively associated with relationship quality. Lifestyle changes were also positively associated with sexual desire, but only for participants with high (vs. low) fear of COVID-19 infection. For these participants, sexual desire was associated with positive changes in one's sex life and wanting to spend time with one's partner, but not with overall relationship quality. Results were consistent after controlling for pandemic-related anxiety and demographic variables. This study advances literature focused on the importance of romantic relationships in stress-provoking situations such as the COVID-19 pandemic by shedding light on the association between sexual desire and personal and relational well-being.